1992
DOI: 10.12968/jowc.1992.1.3.20
|View full text |Cite
|
Sign up to set email alerts
|

A trial of a hydrocolloid dressing in the management of indolent ulceration

Abstract: A report of a randomised, controlled trial of a hydrocolloid dressing used in the treatment of leg ulcers that were failing to heal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…From those included, 22 studies 30–51 evaluated the use of modern vs. conventional dressings, and nine 52–60 were comparative studies of different modern dressings. Twenty‐six studies 30–48,52–58 corresponded to ulcers of venous origin and five 49–51,59 , 60 to leg ulcers whose etiology was not clearly identified. No study that exclusively targeted arterial ulcers and met the inclusion criteria was identified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From those included, 22 studies 30–51 evaluated the use of modern vs. conventional dressings, and nine 52–60 were comparative studies of different modern dressings. Twenty‐six studies 30–48,52–58 corresponded to ulcers of venous origin and five 49–51,59 , 60 to leg ulcers whose etiology was not clearly identified. No study that exclusively targeted arterial ulcers and met the inclusion criteria was identified.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies 36,37 , 52,54 , 59 made no reference to the size of the wound to be treated, and four failed to describe the baseline characteristics of the study population 36,37 , 44,59 . Seven studies made explicit mention of the fact that results were analyzed on an intention‐to‐treat basis 33,38 , 42,44 , 47,53 , 60 and only two 40,42 described the a priori calculation of the number of patients needed in order to be able to detect a clinical difference as statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ISSN 2788-9580 (en línea) ISSN 0014-1445 (impreso) eca Estudios Centroamericanos Finalmente, aplicar estrategias metacognitivas en el aprendizaje-enseñanza de las lenguas extranjeras permite a los estudiantes de lenguas asegurar una educación con (1) autonomía, al ser capaces de seleccionar y secuenciar sus propias actividades y materiales; (2) colaboración, al lograr organizar equipos de trabajo en los que sus miembros se apoyen mutuamente; y (3) integración, al ser capaces de entrelazar todos los conocimientos con las estructuras ya existentes en su mente (Moffett & Wagner, 1992;Tesouro, 2005).…”
Section: La Metacognición En El Proceso De Enseñanza-aprendizaje De L...unclassified